Jedi Academy. At last, Jedi - Krosoczka, Jarrett (Scholastic Inc., 2020)
Christina Starspeeder and her fellow Jedi apprentices return to the planet Coruscant where they're told to stay put while their masters hunt for villains Goonga the Hutt and Krio Vin, Christina's father. But when Christina's brother Victor goes missing, she sets out on a mission to find him.